The Influence Work-Life Balance, Perceived Organizational Support and Intrinsic Motivation to Employee Performance PT. MC (Mutiara Cahaya Slawi) In Tegal Regency - Zulfikri, Moh. Danar; endratno, hermin; Suyoto, Suyoto; Innayah, Maulida Nurul (PT FORMOSA CENDEKIA GLOBAL, 2025)
The purpose of this study is to examine the effect of Work Life Balance, Perceived Organizational Support, and Intrinsic Motivation on Employee Performance at PT MC (Mutiara Cahaya) Slawi in Tegal Regency. This study uses a quantitative approach with a purposive sampling technique involving 98 contract employees with a minimum of 6 months of work and permanent employees. Data collection was carried out online on Google from, and analyzed using the Structural Equation Modeling Partial Least Squares (SEM-PLS) method on SmartPLS 3.0 Software to test the relationship between variables. The results of this analysis indicate that work life balance has a positive but insignificant effect on performance, Perceived Organizational Support does not affect employee performance, while Intrinsic motivation has a significant positive effect on employee performance. With this research, the company is expected to create a balance of daily life and organizational support where the organization assesses contributions and cares about the welfare of employees. The implications of this study for supermarket management, the need to design policies that support intrinsic motivation of staff and provide work life balance in providing continuous improvement of employee performance.